ANALYSIS FOR SOLENOID VALVE FAILURE BASED ON MULTI-PHYSICS FINITE ELEMENT MODEL - LI JianFeng; XIAO MingQing; TANG XiLang; SHI WeiWen; WANG RuoAn (Jixie qiangdu)
An accelerated life test is designed and a kind of analysis method for solenoid valve failure based on multi-physics finite element model is put forward due to the uncertainty of failure mechanism and the lack of effective means to analyze faults. Firstly, the model of temperature field is built based on ANSYS finite element software and the temperature distribution of components is calculated. Then, the temperature is added to the mechanical stress field as the new load and the coupling stress is received based on the combined action of thermal stress and mechanical stress. Finally, a kind of degradation failure mechanism of the solenoid valve, through the comparison of experimental data and simulation results, is obtained based on the comprehensive analysis of temperature and coupling stress. The result shows the high temperature produced by coils can fail the insulation between coil wires. Meanwhile, the coupling effect of thermal stress caused by high temperature and the mechanical stress can squeeze coils resulting in the continuous short-circuit of coils. When the electromagnetic force of iron core is lower than its threshold, the iron core will not overcome the elasticity to move up and down and finally the failure of the SV will happen. This prediction method can be widely applied to the other fault diagnosis types of degradation failure of solenoid valves. The result can be provided for the optimization and researched on prolonging life of the solenoid valve.